Does past participation in competitive sports affect the relationships between socioeconomic factors and self-rated health: study randomly selected Polish male and female former athletes and non-athletes - Donata Woitas-Ślubowska; Elżbieta Hurnik; Anna Skarpańska-Stejnborn; Rafał Gotowski (Kazimierz Wielki University, 2018)
Objectives: Identifying patterns of associations between self-rated health (SRH) and socioeconomic factors in male and female former athletes and non-athletes, and verifying if these associations are modified by the factors which characterize former athletes` past sport participation. Methods: The data used came from Former Athletes' Lifestyle Project conducted among former athletes (N=351) and non-athletes (N=466) aged 18-66 years randomly selected from three regions of Poland. Anonymous questionnaires regarding SRH, socioeconomic variable, and factors which characterize former athletes' past sport participations (competitive sports training experience, sport level achieved in the past, and period of time since the end of sports career) were used. SRH was categorized as negative (average, poor or very poor) and positive (good or very good). Multiple logistic regression analyses were used to calculate the odds ratios of negative SRH after adjusting for socioeconomic and sports characteristics. Results: Groups former athletes and non-athletes exhibited different patterns of relationships between SRH and socioeconomic variables. In both male and female non-athletes the higher risks of negative SRH were significantly associated with low socioeconomic position. Short time from ending sport careers significantly reduced the risk of negative SRH in both male and female former athlete. Conclusions: Among men and women former participation in competitive sports limits the adverse effect of socioeconomic status on SRH. For this reason it appears to be appropriate to incorporate popularization of competitive sport as one of the strategies of public health indirectly oriented towards reduction in socioeconomic inequalities in health.